Hydroxylated fluorescent dyes for live-cell labeling: synthesis, spectra and super-resolution STED - Butkevich, Alexey N.; Engelhardt, Johann; Hell, Stefan (Chemistry - a European journal, 2017)
Hydroxylated rhodamines, carbopyronines, silico- and germanorhodamines with absorption maxima in the range of 530-640 nm were prepared and applied in specific labeling of living cells. The direct and high-yielding entry to germa- and silaxanthones tolerates the presence of protected heteroatoms and may be considered for the syntheses of various sila- and germafluoresceins, as well as -rhodols. Application in stimulated emission depletion (STED) fluorescence microscopy revealed a resolution of 50-75 nm in one- and two-color imaging of vimentin-HaloTag fused protein and native tubulin. The established structure-property relationships allow for prediction of the spectral properties and the positions of spirolactone/zwitterion equilibria for the new analogues of rhodamines, carbo-, silico-, and germanorhodamines using simple additive schemes.
First published: 29 March 2017
Gesehen am 24.10.2018